Rapamycin Preserves Neural Tissue, Promotes Schwann Cell Myelination and Reduces Glial Scar Formation After Hemi-Contusion Spinal Cord Injury in Mice - Liu, Junhao; Li, Ruoyao; Huang, Zucheng; Lin, Junyu; Ji, Wei; Huang, Zhiping; Liu, Qi; Wu, Xiaoliang; Wu, Xiuhua; Jiang, Hui; Ye, Yongnong; Zhu, Qingan (Frontiers in Molecular Neuroscience, 2021)
Protecting white matter is one of the key treatment strategies for spinal cord injury (SCI), including alleviation of myelin loss and promotion of remyelination. Rapamycin has been shown to neuroprotective effects against SCI and cardiotoxic effects while enhancing autophagy. However, specific neuroprotection of rapamycin for the white matter after cervical SCI has not been reported. Therefore, we aim to evaluate the role of rapamycin in neuroprotection after hemi-contusion SCI in mice. Forty-six 8-week-old mice were randomly assigned into rapamycin group (n=16), vehicle group (n=16), and sham group (n=10). All mice of rapamycin and vehicle groups were received a unilateral contusion with 1.2 mm displacement at C5 and followed by daily intraperitoneal injection of rapamycin or dimethyl sulfoxide solution (1.5 mg·kg-1·day-1). The behavioral assessment was conducted before the injury, 3 days and every two weeks post-injury (WPI). The autophagy-related proteins, the area of spared white matter, the number of oligodendrocytes (OLs) and axons were evaluated at 12 WPI, as well as the glial scar and the myelin sheaths formed by Schwann cells at the epicenter. The 1.2-mm contusion led to a consistent moderate-severe SCI in terms of motor function and tissue damage. Rapamycin administration promoted autophagy in spinal cord tissue after injury and reduced the glial scar at the epicenter. Additionally, rapamycin increased the number of OLs and improved motor function significantly compared with the vehicle group. Furthermore, the rapamycin injection resulted in an increase of Schwann cell-mediated remyelination and weight loss. Our results suggest that rapamycin can enhance autophagy, promote Schwann cells myelination and motor function recovery by preserved neural tissue, reduced glial scar after hemi-contusive cervical SCI, indicating a potential strategy for SCI treatment.